A concise synthesis of single components of partially sulfated oligomannans. Issue 47 (14th October 2015) - Tony Mong, Kwok-Kong; Shiau, Kai-Sheng; Lin, Yu Hsien; Cheng, Kuang-Chun; Lin, Chun-Hung
Abstract : The synthesis of polysulfated α(1 → 3)/α(1 → 2)-linked oligomannans using the DMF-modulated glycosylation method is reported. Abstract : A concise synthesis of single components of C2 sulfated oligomannans including trimers, tetramers, and pentamers is reported. The synthesis features the application of the DMF-modulation method for the participatory thiomannoside donors in 1, 2- trans α-glycosidic bond formation. The obtained oligomannans were fully characterized using 1 H, 13 C, COSY, and HSQC NMR spectroscopy.